Permafrost thaw and soil moisture driving CO2 and CH4 release from upland tundra. Issue 3 (25th March 2015) - Natali, Susan M.; Schuur, Edward A. G.; Mauritz, Marguerite; Schade, John D.; Celis, Gerardo; Crummer, Kathryn G.; Johnston, Catherine; Krapek, John; Pegoraro, Elaine; Salmon, Verity G.; Webb, Elizabeth E.
Abstract As permafrost degrades, the amount of organic soil carbon (C) that thaws during the growing season will increase, but decomposition may be limited by saturated soil conditions common in high‐latitude ecosystems. However, in some areas, soil drying is expected to accompany permafrost thaw as a result of increased water drainage, which may enhance C release to the atmosphere. We examined the effects of ecosystem warming, permafrost thaw, and soil moisture changes on C balance in an upland tundra ecosystem. This study was conducted at a water table drawdown experiment, established in 2011 and located within the Carbon in Permafrost Experimental Heating Research project, an ecosystem warming and permafrost thawing experiment in Alaska. Warming and drying increased cumulative growing season ecosystem respiration by 20% over 3 years of this experiment. Warming caused an almost twofold increase in decomposition of a common substrate in surface soil (0–10 cm) across all years, and drying caused a twofold increase in decomposition (0–20 cm) relative to control after 3 years of drying. Decomposition of older C increased in the dried and in the combined warmed + dried plots based on soil pore space 14CO2. Although upland tundra systems have been considered CH4 sinks, warming and ground thaw significantly increased CH4 emission rates. Water table depth was positively correlated with monthly respiration and negatively correlated with CH4 emission rates. These results demonstrate that warming and drying may increase loss of old permafrost C from tundra ecosystems, but the form and magnitude of C released to the atmosphere will be driven by changes in soil moisture.